2014
DOI: 10.1371/journal.pone.0097404
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology and Molecular Epidemiology of Enterovirus 71 in Russia

Abstract: Enterovirus 71 (EV71) is an emerging human pathogen causing massive epidemics of hand, foot and mouth disease with severe neurological complications in Asia. EV71 also circulates in Europe, however it does not cause large outbreaks. The reason for distinct epidemiological patterns of EV71 infection in Europe and Asia and the risk of EV71 epidemic in Europe and Russia remain unknown. Seroepidemiology of EV71 and molecular epidemiology of occasional EV71 isolates were studied to explore circulation of EV71 in Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…Studies conducted in northern China reported a higher EV71 seroprevalence although the southern areas tend to have longer periods of EV71 activity with two epidemics in some years [7]. However several large outbreaks of HFMD have been reported in northern China recently [73, 74]. Russia, a high-latitude country, also reported a relatively higher seroprevalence (83% in children 5 years) but with lower HFMD incidence in a recent study [73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in northern China reported a higher EV71 seroprevalence although the southern areas tend to have longer periods of EV71 activity with two epidemics in some years [7]. However several large outbreaks of HFMD have been reported in northern China recently [73, 74]. Russia, a high-latitude country, also reported a relatively higher seroprevalence (83% in children 5 years) but with lower HFMD incidence in a recent study [73].…”
Section: Discussionmentioning
confidence: 99%
“…However several large outbreaks of HFMD have been reported in northern China recently [73, 74]. Russia, a high-latitude country, also reported a relatively higher seroprevalence (83% in children 5 years) but with lower HFMD incidence in a recent study [73]. Although higher environmental temperatures and humidity are associated with the higher HFMD incidence in China [7577], HFMD occurrence is likely to be driven by a range of factors not limited to environmental conditions, such as population structure, birth rates, urbanization and the prevalent circulating strains [63, 75, 78].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the study of EV71 mainly focused on the investigation of outbreak, 19 the analysis of severe cases, 20 the surveillance of molecular epidemiology, 21 and the evaluation of EV71 vaccine efficacy. 22,23 This study, based on 2 large-scale phase 3 clinical trials of an inactivated EV71 vaccine, we estimated the economic and health burden of EV71 associated-disease using the TAPQOL questionnaire to provide valuable information for both those researching the cost-effectiveness analysis of EV71 vaccine and those who make policies regarding the plan or allocation of health resources.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, EV71 has caused several large-scale epidemic outbreaks throughout the world, especially in the Asia-Pacific region (2)(3)(4). These outbreaks caused significant morbidity and mortality and severely endangered the public health (5).…”
mentioning
confidence: 99%